The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/2365945
|View full text |Cite
|
Sign up to set email alerts
|

PostoperativeNocardiaEndophthalmitis and the Challenge of Managing with Intravitreal Amikacin

Abstract: Nocardia is a rare cause of delayed onset postoperative endophthalmitis after cataract surgery and it usually carries a guarded visual prognosis. Purpose. To highlight the clinical presentation, microbiological profile, and treatment outcome in a case of nocardial endophthalmitis after manual small incision cataract surgery. Methods. This case report highlights the typical features of Nocardia endophthalmitis, which presented six weeks after undergoing small incision cataract surgery. The case was managed by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Only after a later microbiological sample yielded a negative result; was the oral sulfamethoxazole/trimethoprim combination discontinued 12. While some cases required more than 3 months of systemic medication,13 other authors have reported favourable outcomes for N. endophthalmitis after 6–10 weeks of oral therapy 14 30. According to Sharma and O’Hagan,31 the infection resurfaced following the application of topical steroids, requiring reintroduction of oral sulfamethoxazole/trimethoprim.…”
Section: Discussionmentioning
confidence: 99%
“…Only after a later microbiological sample yielded a negative result; was the oral sulfamethoxazole/trimethoprim combination discontinued 12. While some cases required more than 3 months of systemic medication,13 other authors have reported favourable outcomes for N. endophthalmitis after 6–10 weeks of oral therapy 14 30. According to Sharma and O’Hagan,31 the infection resurfaced following the application of topical steroids, requiring reintroduction of oral sulfamethoxazole/trimethoprim.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 , 18 , 19 ] It has been reported that vitreous body injection of amikacin may lead to macular necrosis. [ 20 , 21 ] However, there are no effective antibiotics that can control infection through anterior chamber injection. In addition, the iris has significant inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…An incorrect diagnosis is often assumed, and a more common pathogen of mycotic origin is then considered. Because of the delayed causal treatment in these types of cases, significant ocular morbidity, including enucleation of the eye, cannot be prevented in most cases [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%